ANALISIS PELAKSANAAN PROMOSI PADA PT. BANK DANAMON TBK CABANG BAGANSIAPIAPI - ", Fatimah; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Promotionisthe effortsmadebythe companymoneyin order tonotify, informaboutthecompanyandtheir productsin the form ofservices andproductsto the middle-finished goodssociety, clientsorcustomers, so that theproductbeknownandusedbycustomerswiththeconvenience and benefitsof all forms ofpromotiongiven.This research was conductedat PT. Bank DanamonTbk Branch BagansiapiapiCommerceRoad RT 06 RW 01Bagansiapiapi. The purposeof this studywas conducted toanalyzethe implementation ofthe promotion ofthePT. BankDanamonTbkBranchBagansiapiapiIn this study,the methodology usedisdescriptivestatistics, wherethe sampleused istheBankBranchBagansiapiapicustomersandas a sourceof informationistheHR,marketingmanager, todetermine the sampleusing theformulaSlovin, withaccidentalsamplingmethod ofsampling, data collectionthroughinterviewtechniques, questionnaire.From the analysis ofthe implementation ofthe campaign carried outbyPT.BankDanamonTbkBranchBagansiapiapiwhichincludesadvertising, personal selling, salespromotion, statingthatsuch promotional activitiesareinboth categories with apercentage ofthedistancebetween thenotesis very goodwithverylittlepoorly.Keywords: promotion, advertising, sales promotion, personal selling